NKCC1: Newly Found as a Human Disease-Causing Ion Transporter. Issue 1 (3rd November 2020) - Koumangoye, Rainelli; Bastarache, Lisa; Delpire, Eric
Abstract: Among the electroneutral Na + -dependent chloride transporters, NKCC1 had until now evaded identification as a protein causing human diseases. The closely related SLC12A transporters, NKCC2 and NCC have been identified some 25 years ago as responsible for Bartter and Gitelman syndromes: two renal-dependent salt wasting disorders. Absence of disease was most surprising since the NKCC1 knockout mouse was shown in 1999 to be viable, albeit with a wide range of deleterious phenotypes. Here we summarize the work of the past 5 years that introduced us to clinical cases involving NKCC1. The most striking cases are of 3 children with inherited mutations, who have complete absence of NKCC1 expression. These cases establish that lack of NKCC1 causes deafness; CFTR-like secretory defects with mucus accumulation in lung and intestine; severe xerostomia, hypotonia, dysmorphic facial features, and severe neurodevelopmental disorder. Another intriguing case is of a patient with a dominant deleterious SLC12A2 allele. This de novo mutation introduced a premature stop codon leading to a truncated protein. This mutant transporter seems to exert dominant-negative effect on wild-type transporter only in epithelial cells. The patient who suffers from lung, bladder, intestine, pancreas, and multiple endocrine abnormalities has, however, normal hearing and cognition. Finally, new reports substantiate the haploinsufficiency prediction of the SLC12A2 gene. Cases with single allele mutations in SLC12A2 have been linked to hearing loss and neurodevelopmental disorders. Graphical Abstract: